"It was no different to a prison camp": Oral accounts of adaptations, transitions and surviving an "emergency camp"; from Sophiatown to Ammunition Depot 91, 1955–1960s - Leta, Lesiba T. (HTS teologiese studies, 2021)
The demolition of Sophiatown, Cato Manor, District Six and other areas under the apartheid regime hugely impacted the socio-economic lives of various South Africans (particularly those people classified as non-whites). The classification of South African cosmopolitan townships as slums according to the Slums Act of 1934, and the ambitions of achieving social segregation, resulted in the geographical separation of races facilitated by the Group Areas Act of 1950. The act legally justified the forced removal of Indian families from Sophiatown. Then, they were temporarily placed in a military base next to Lenasia. Through the use of oral interviews, this article interrogates the unknown history of the Indian families in their transitional period from Sophiatown to Ammunition Depot 91 (also referred to as the ‘military camp/military base’ in Lenasia). Furthermore, the article sheds light on their untold experiences; particularly on the arrival of Indian families in the military camp, their living conditions, health-related matters, the utilisation of coping mechanisms such as religion and recreational activities, perceptions about their stay, effects on transportation and their general experiences in the transition camp. The article accentuates the rapid nature of these removals particularly in Sophiatown which resulted in the lack of adequate alternative accommodation for the Indian residents.Contribution: The article offers fresh perspectives for deeper interrogation of the consequences of forced removals in apartheid South Africa, by reflecting on the memories and lived experiences of interviewees in a case study that has hitherto not been addressed by social historians.